Dampak Dwibahasa terhadap Komunikasi dan Sosial Emosional pada Anak Usia 3-4 Tahun - Hasna Laila Rahman; Masnipal; Dewi Mulyani (Jurnal Riset Pendidikan Guru Paud, 2024)
Abstrak. Manusia membutuhkan komunikasi untuk hidup, dengan bahasa sebagai alat paling efektif untuk menyampaikan pesan, pikiran, dan perasaan. Bahasa memungkinkan kerja sama antar manusia dan dominan dalam berbagai aktivitas. Penelitian ini mengkaji dampak dwibahasa pada perkembangan komunikasi, sosial, dan emosional anak usia dini. Dengan meningkatnya jumlah keluarga dwibahasa, penting memahami bagaimana pengalaman ini memengaruhi perkembangan anak. Permasalahan yang dikaji meliputi dampak dwibahasa terhadap: (1) komunikasi anak, (2) sosialisasi dengan teman sebaya, dan (3) perkembangan emosi. Penelitian menggunakan metode kualitatif dengan studi kasus, melibatkan observasi dan wawancara terhadap orang tua, guru, dan dua anak perempuan usia 3 dan 4 tahun di lingkungan dwibahasa. Hasil menunjukkan dwibahasa dapat menyebabkan kesulitan komunikasi, hambatan bersosialisasi, dan masalah emosi seperti kecemasan dan menarik diri. Abstract. Humans need communication for survival and language is the most effective communication tool to convey messages, thoughts, feelings, and goals to others. Language enables cooperation between humans, so its role is very dominant in various daily activities. Therefore, this study aims to examine the impact of bilingualism on communication and social-emotional development in early childhood. With the increasing number of bilingual families in various countries, it will be important to understand how bilingual experiences affect children at this critical stage of development. Based on this phenomenon, the problems in this study are formulated as follows: (1) How does bilingualism impact on children's communication development? (2) How does bilingualism impact on children's socialization among peers? (3) How does bilingualism impact on children's emotional development. The method used in this research is a qualitative method with a case study approach, involving observation and in-depth interviews with parents, teachers, and children in a bilingual environment. The subjects were two girls aged 3 and 4 years old. The results showed that the use of bilingualism in children aged 3-4 years can cause children's inability to communicate fluently, barriers in socializing with peers and barriers in emotions (anxiety & frequent withdrawal).